FINANCIAL LITERACY IN INFLUENCING THE GROWTH OF MSME BUSINESSES MEDIATED BY ACCESS TO FINANCE AND FINTECH ADOPTION: Array - Gilang Kharisma Putra (JASS (Journal of Accounting for Sustainable Society), 2024)
This research aims to test financial literacy, access to finance, and the adoption of fintech in order to encourage business growth among MSME actors, particularly MSME actors in Kendal Regency. In addition to directly testing access to finance and the adoption of fintech, it will also attempt to examine whether access to finance and the adoption of fintech can serve as a link between financial literacy and business growth. The results of this study are expected to provide input and assist the government, especially the Kendal Regency government, in formulating policies that can support MSME actors in enhancing their business growth. This research is an explanatory study aimed at testing the relationships between variables through a quantitative approach (Creswell & Creswell, 2018). The population of this study consists of all MSME actors in Kendal district, totaling 16,508 units. In the sampling process, this research employs purposive sampling techniques. The number of samples in this study is based on the minimum sample size set at 10 times the number of indicators used (Roscoe, 1975). From the 4 variables used in this study, there are a total of 20 indicators, so the minimum sample size in this study is 200 respondents. Of the five hypotheses tested directly, the statistical results show that four hypotheses can be accepted and one hypothesis is rejected. Meanwhile, in the mediation test, access to finance has been proven to mediate the relationship between financial literacy and business growth, while the adoption of fintech is not proven